Analysis of Prognostic Factors in 1041 Patients with Localized Soft Tissue Sarcomas of the Extremities - Pisters, P. W. T. (Institutional Knowledge at Singapore Management University, 1996)
To identify specific independent adverse clinicopathologic factors for event-free survival in a cohort of consecutively treated patients with extremity soft tissue sarcomas. Patients and Methods : Prospectively collected data from a population of 1,041 adult patients with localized (American Joint Committee on Cancer [AJCC] stage IA to IIIB) extremity soft tissue sarcomas were analyzed. Patients were treated at a single institution between 1982 and 1994. Patient, tumor, and pathologic factors were analyzed by univariate and multivariate techniques to identify independent prognostic factors for the end points of local recurrence, distant recurrence, disease-specific survival, and postmetastasis survival. Results : The 5-year survival rate for this cohort of patients was 76%, with a median follow-up time of 3.95 years. Significant independent adverse prognostic factors for local recurrence were age greater than 50 years, recurrent disease at presentation, microscopically positive surgical margins, and the histologic subtypes fibrosarcoma and malignant peripheral-nerve tumor. For distant recurrence, intermediate tumor size, large tumor size, high histologic grade, deep location, recurrent disease at presentation, leiomyosarcoma, and nonliposorcoma histology were independent adverse prognostic factors. For disease-specific survival, large tumor size, high grade, deep location, recurrent disease at presentation, the histologic subtypes leiomyosarcoma and malignant peripheral-nerve tumor, microscopically positive surgical margins, and lower extremity site were adverse factors. For postmetastasis survival, only large tumor size (> 10 cm) was an adverse prognostic factor. Conclusion : The independent adverse prognostic factors for distant recurrence and disease-specific survival differ from those identified for subsequent local recurrence. Patients with microscopically positive surgical margins or patients who present with locally recurrent disease are at increased risk for subsequent local recurrence and tumor-related mortality. Specific histopathologic subtypes are associated with increased risks for local failure and tumor-related mortality.